2015
DOI: 10.1021/acs.energyfuels.5b02428
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Higher-Mass Elements and Surface Functional Groups during the Pyrolysis of Waste Pecan Shell

Abstract: Thermochemical conversion of agricultural wastes to bioenergy has a potential to play forefront roles within the context of the food, energy, and water nexus. The biochar solid product of pyrolysis is a promising tool to manage food crop production and water resources by means of soil amendment. The goal of this study was to understand the fate of surface functional groups and higher-atomic-mass elements during the pyrolysis of pecan shell, which is known to accumulate calcium oxalate. Pecan shell feedstock an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 36 publications
4
33
0
Order By: Relevance
“…This conversion takes place during pyrolysis between 400 and 500°C. as shown using XRD measurements in several studies (Shinogi and Kanri, 2003; Singh et al, 2010; Perez‐Rodriguez et al, 2011; Kloss et al, 2012; Al‐Wabel et al, 2013; Wang et al, 2014, 2015; Jones et al, 2015). Here, a full conversion of calcium oxalate into calcite (calcium carbonate) was clearly shown in biochars produced from poplar bark at 450°C.…”
Section: Discussionmentioning
confidence: 53%
“…This conversion takes place during pyrolysis between 400 and 500°C. as shown using XRD measurements in several studies (Shinogi and Kanri, 2003; Singh et al, 2010; Perez‐Rodriguez et al, 2011; Kloss et al, 2012; Al‐Wabel et al, 2013; Wang et al, 2014, 2015; Jones et al, 2015). Here, a full conversion of calcium oxalate into calcite (calcium carbonate) was clearly shown in biochars produced from poplar bark at 450°C.…”
Section: Discussionmentioning
confidence: 53%
“…The disintegration of biochar pellets was not observed at lower biochar loadings (Figure S7 top), when low pyrolysis temperature biochar was employed (PS350 in Figure S7 , bottom), or when nC 60 -sonicate was employed instead of nC 60 -stir. Higher temperature biochars have higher attrition 41 to form smaller particles by mechanical forces 42 , 43 . Higher biochar loading could enhance the mechanical crushing of biochar pellets during the end-over-end rotation in the presence of nC 60 -stir.…”
Section: Resultsmentioning
confidence: 99%
“…3 ), and thus could originate from CaCO 3 in pecan shell biochar (Fig. 1 ) 41 . It is inherently challenging to distinguish two carbon materials (char and C 60 ) by TEM because of low contrast and overlapping projection 30 , 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Considering the importance of the product generated from pyrolysis, studies have found suitable conditions of this technique to evaluate the behavior of elements and functional groups present in pecan shells. It was found that in a temperature range between 300 and 500 ºC, changes occurred and the removal of functional groups from the surface of the pyrolysis product generated, as well as a change in the shell structure, and an increase of gaseous products, such as methane, carbon dioxide, and ethane [47]. In addition, other studies have reported the adsorptive capacity of pecan waste materials from the application of pyrolysis.…”
Section: Gasification and Pyrolysismentioning
confidence: 99%